Dengue Hemorrhagic Fever in Bima City: A Study - Asryadin Asryadin; Adhi Aqwam; Rizka Khairunnisa; Hetti Koes Endang; Rosita Rosita; Fahrul Annas; Hasan Hasan (Jurnal Penelitian Pendidikan IPA, 2023)
Cases of Dengue Hemorrhagic Fever (DHF) in Bima City are of concern because of its widespread spread and the number of sufferers continues to grow. The Municipal Government of Bima, West Nusa Tenggara, has established an Extraordinary Event (KLB) status for DHF. This status was assigned as a response to the high increase in DHF cases over the past two months, namely January and February 2023. Although vector control efforts have been made, DHF cases continue to fluctuate and increase significantly in early 2023. Therefore, researchers have conducted a Quick Response Analysis of DHF cases in Bima City with the aim of providing information about DHF cases and analyzing this information, as well as developing recommendations for alternative solutions in preventing an increase in DHF cases in Bima City. Through the descriptive method, it was found that the incidence of DHF in Bima City tends to increase significantly at the beginning of 2023 compared to the previous two years, with 172 positive cases and 4 of them leading to death as of February 10, 2023. One of the things of concern based on the case analysis is the understanding and attitude of the community regarding environmental sanitation. Meanwhile, solutions that can be recommended are in the form of short, medium, and long term recommendations which can be used as a reference for consideration in establishing regulations to control dengue fever